Knowledge, Attitude, and Concerns of Saudi Parents Regarding Human Papillomavirus Vaccine - Ahmed A. Alsaati; Roudin H. Alhasawi; Amjad S. Alzahrani; Omnia A. Sulimani; Reem A. Alshahrani; Raghad O. Almasoudi; Mazin M. Aljabri (Journal of Dermatology and Dermatologic Surgery)
Background: Vaccines against human papillomaviruses (HPVs) can prevent infection and lower the risk of cervical cancer in women. Purpose: The purpose of the study was to assess parents’ awareness level and hesitancy toward HPV vaccination of their children. Methods: This cross-sectional study recruited Saudi parents who visited Maternity and Children Hospitals, Makkah, Saudi Arabia. Results: A total of 591 parents were enrolled. About 49% of the parents have not heard about HPV before. Only 34% and 39.4% knew that HPV causes cervical cancer and that vaccination protects against cervical cancer, respectively. About one-third (30.3%) reported that they knew that HPV vaccine can be offered to female children 9 years old and above, and 80.2% had poor awareness level of the HPV. For those not planning to give their children the vaccination, the most reported reasons included lack of knowledge about the vaccine (40.7%) and not being recommended by medical staff (17.3%). The most reported source of information was social media (21.3%). Only 7% of parents vaccinated their children, and 55% planned to do so. Poor awareness was significantly associated with older age (P = 0.001), fathers (P = 0.002), having partially vaccinated children (P = 0.001), and the internet as an information source (P = 0.001). Conclusion: The parents’ awareness level is poor regarding HPV infection and vaccination. The rate of children’s vaccination is very low. The identified causes of hesitancy should be targeted in future projects to increase vaccine coverage. Social media and the Internet can be utilized to disseminate reliable information about HPV and its vaccine to a large group of audience.